(untitled) (Clinics, 2013)
OBJECTIVES: Myeloid-derived suppressor cells contribute to the immunosuppressive microenvironment during tumor development and limit the efficacy of cancer immunotherapy. Identifying myeloid-derived suppressor cells and associated factors is the first step in creating strategies to reverse the suppressive effects of these cells on the immune system. METHODS: To induce lung cancer, we administered 2 doses of urethane to BALB/c mice and observed these animals for 120 days. After this period, we evaluated the percentage of myeloid-derived suppressor cells in the blood, lung and bone marrow. The expression of alpha-smooth muscle actin, transforming growth factor-β, Toll-like receptor 2, Toll-like receptor 4, and interleukin-6 was also determined in the lung tissue. RESULTS: Myeloid-derived suppressor cells were increased in all evaluated tissues after lung cancer development in association with increased Toll-like receptor 4 expression and decreased interleukin-6 expression in the lung. We observed alpha-smooth muscle actin and transforming growth factor-β expression in lung nodules. CONCLUSIONS: We believe that the early diagnosis of cancer through determining the blood levels of myeloid-derived suppressor cells followed by the depletion of these cells should be further investigated as a possible approach for cancer treatment.